"African Know Thyself": Epistemic Injustice and the Quest for Liberative Knowledge. Issue 2 (3rd July 2017) - Mungwini, Pascah
ABSTRACT: This article is framed against the historic myth of emptiness and its consequences on Africa, and takes a closer look at the project of modernity and the question of epistemic injustice in Africa. It deploys the phrase "African know thyself" to capture the need for Africans to grasp the distinctive particularity of their history as a people of equal ontological standing with the rest of humanity. This injunction affords special significance to history and its role in shaping the philosophical agenda in Africa by reminding us that philosophic discourse originates from, and is linked to the concrete conditions of existence, out of which it is formulated. To address the problem of epistemic injustice, Africans need to become more critically conscious of themselves and their situation in ways that inform their intellectual practice. This author submits that philosophy in Africa should assist in both "re-writing and re-righting" Africa's position in the global knowledge landscape.